Syntactic Priming in Comprehension: Evidence from Event-Related Potentials - Ledoux, Kerry; Traxler, Matthew J.; Swaab, Tamara Y. (Psychological science, 2007)
Syntactic priming is the facilitation of processing that occurs when a sentence has the same syntactic form as a preceding sentence. Such priming effects have been less consistently demonstrated in comprehension than in production, and those that have been reported have depended on the repetition of verbs across sentences. In an event-related potential experiment, subjects read target sentences containing reduced-relative clauses. Each was preceded by a sentence that contained the same verb and either a reduced-relative or a main-clause construction. Reduced-relative primes elicited a larger positivity than did main-clause primes. Reduced-relative targets that were preceded by a main-clause prime elicited a greater positivity than the same target sentences following a reduced-relative prime. In addition, syntactic priming effects were dissociated from effects of lexical repetition at the verb.